Upaya Antisipasi Burnout pada Staf Instalasi Gawat Darurat Pasca Transformasi Rumah Sakit - Dyah Retno Andayani Puspitorini; Ernawaty Ernawaty (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the causes of burnout among Emergency Department (ED) staff post-hospital transformation and to develop anticipatory strategies to mitigate burnout risk. The research employed a quantitative approach using the Maslach Burnout Inventory (MBI) scale to measure burnout levels among ED staff at RSUD Husada Prima. The research population consisted of 25 individuals, and data collection was conducted on December 26, 2022. The findings indicate that the majority of respondents experienced moderate burnout (88%), with variations based on gender, age, marital status, educational level, job status, and work tenure. Recommendations for mitigating burnout include interpersonal skills training, improving the work environment, workload management, recognition and reward systems, professional development opportunities, regular meetings with supervisors, employee wellness programs, workload adjustments according to age and tenure, and education about burnout symptoms. Keywords: Burnout, Emergency Department, Health Workers, Hospital, Transformations